BIOSILO DE RESIDUOS DE MERLUZA Y HARINA DE CEBADA FERMENTADOS CON BACTERIAS ÁCIDO LÁCTICAS SELECCIONADAS - EMILIO MARGUET; MARISOL VALLEJO; GUSTAVO SCHULMAN; CECILIA IBAÑEZ; PABLO LEDESMA; ROMINA PARADA (Biotecnología en el Sector Agropecuario y Agroindustrial, 2017)
Suitability of Lactococcus lactis Tw34 and Lactobacillus plantarum Lb7 as bio-silage inoculants was studied. Experiments were carried out with a mixture of hake (Merluccius hubbsi) by-products and barley meal fermented during 7 days. A sample acidified with lactic acid was used as control. In biological mixtures, the pH dropped below 5,0 after 2 days of fermentation and remained stable until the end of the experience. Maximum populations (> 109 CFU/g) were reached after 5 days of incubation at 18°C. Water soluble peptides concentration increased during the 7 days of incubation and no significant differences (p < 0,05) were found between the control and both bio-silage. Trichloroacetic acid soluble peptides concentrations of bio-silages were higher than the control (p > 0,05). After 7 days, phosphorous concentrations reached 2.26 and 2,42 g/100 g in bio-silages fermented with Lc. lactis Tw34 and Lb. plantarum Lb7, respectively, while control values remains almost stable (1,61 g/100 g). At the end of the experience, inhibitory activity of trypsin was abolished in both bio-silage while in control sample antinutritional factors remained active. The results indicated the feasibility of the use of the selected mixture as substrate for bio-silage production and the effectiveness Lc. lactis Tw34 and Lb. plantarum Lb7 as inoculants.